The Centralization and Decentralization of Telemedicine Networks in Korea and Japan - Soo-kyung Park (Netcom)
This study scrutinizes telemedicine networks with regard to regionalization and the propensities and determinants of core telemedicine users (doctors and patients) by employing two case areas, Choongbook in Korea and Kagawa in Japan. According to the results, telemedicine networks in Choongbook are dominated by an inter-regional level (in particular, a national level), and most of the telemedicine networks are observed between clinical sites in Choongbook and tertiary care centers in Kyunggi. In contrast, telemedicine networks in Kagawa are dispersed within the diagnostic boundary of Kagawa at a regional level. Interviews with crucial decision-makers revealed the reasons why many patients enjoy health care via telemedicine at an inter-regional level, which include psychological considerations regarding quality and level of health care services, personal stakes in telemedicine service sites, acceptability and credibility of good tertiary care centers, and easy access to and use of medical institutions. In Kagawa, both the existing health care system and the telemedicine system support the maintenance of stable regional health care within Kagawa. Importantly, human relationships based on the regional health care system contribute to creating telemedicine networks within the original purpose of the telemedicine system regarding regionalization. Also, telemedicine’s technological value, convenience, and utility are associated with the regionalization of telemedicine networks within one diagnostic area.